ROCK TYPE ANALYSIS IN BATURAJA FORMATION CARBONATE RESERVOIR, OURO FIELD, NORTH WEST JAVA BASIN - Abdul Aziz, Faisal
Ouro Fields is a hydrocarbon fields that located in North West Java Basin. Generally, carbonat reservoir has a non linear relationship between porosity and permeability, depends on how the reservoir deposited and post deposition process. Carbonate reservoir in Ouro Fields has heteroginity, thus rock type (RT) analysis important to do, for the support of Ouro Fields development. The scopes of this research are lithofacies, facies association, diagenetic, rock type, rock type prediction and relationship analysis between rock type, facies and diagenetic process in Baturaja Formation, Ouro Fields. Available data for this research is 27 well of wireline logs, 26 Routine Core Analysis (RCAL), eight photo of petrograpy and four points of X-Ray Diffraction (XRD). Research done by implementing petrophysics analysis aims to know and clasissify rock properties and RT predictions, lithofacies analysis aims to know the rock characteristics and diagenetic analysis aims to know the process that happened post deposition that affect the quality of rock properties. Based on lithofacies analysis, in Baturaja Formation, Ouro Fields identified five lithofaceis, they are: Mudstone, Foraminifera Packstone, Skeletal, Packstone, Foraminifera Wackestone, and Large Benthic Foraminifera Packston. Based on those six facies analysis there’s three facies association of Baturaja Formation in Ouro Filed there are: Basin Margin, Platform Margin Reef, and Platform Interior. Diagenetic process that occurs in Ouro Fields is micritization, sementation, dissolution, moldic, neomorphism and burial. With the diaegenetic zone marine phreatic, meteoric phreatic and burial. Fflow Zone Indicator (FZI) and Reservoir Quaily Index (RQI) methods used for the RT analysis, those two methods group rock type into discrete rock type (DRT), FZI and RQI method shows the relationship between permeability and porosity with coefficient correltion value. There are six DRT at Ouro Fields, they are: DRT 7 (intercrystalline 10%, moldic 35% and vuggy 55%), DRT 8 (intercrystalline 30% and intraparticle 70%), DRT 9 (intercrystalline 40%, intraparticle 35%, fracture 15% and vuggy 10%), DRT 10 (intercrystalline 10%, intraparticle 30% and vuggy 60%), DRT 11 (vuggy 70%, intercrystalline 10% and moldic 20%), and DRT 13 (vuggy 60%, interparticle 15% and intraparticle 25%). RT prediction had to be done for the well that doesn’t have porosity and permeability value with Multi Resolution Graph Based Clustering (MRGC) method using gamma ray, density and neutron logs as the parameters.Resulting 26 of electrofacies cluster model that has the most suitable prediction to represent five RT from RCAL. Based on analysis of relationship between rock type with porosity types, quality of carbonate rocks on each rock type controlled by the type of porosity and the porosity composition.